Impact of Non-Financial Rewards on Employee Motivation - Kumar, Dhanonjoy; Hossain, Md. Zakir; Nasrin, Mst. Shahnaz (Asian Accounting and Auditing Advancement, 2018)
Employees are viewed as an important element and considered the human capital of any organization. Employees will perform their duties diligently and act if they are motivated and satisfied. De-motivated employees are likely to put in little or no effort in their jobs, produce low-quality work, mostly avoid their workplace, and even exit the organization when they have available opportunities. On the other hand, employees who are motivated to work are likely to be determinant, innovative and competent. Motivated employees are content, dedicated, and work enthusiastically, resulting in the optimum level of employee retention, loyalty, and harmony. These aspects contribute significantly to the growth and development of the overall organization. This study is conducted to measure the impact of non-financial rewards on employee motivation in different organizations in Bangladesh. The results indicate that a significant impact on non-financial rewards contributes to employee motivation. There is a positive correlation between non-financial rewards and employee motivation.